Spectral Distribution of Transport Operator Arising in Growing Cell Populations - Hongxing Wu; Shenghua Wang; Dengbin Yuan (Journal of Function Spaces)
Transport equation with partly smooth boundary conditions arising in growing cell populations is studied in Lp  (1<p<+∞) space. It is to prove that the transport operator AH generates a C0 semigroup and the ninth-order remainder term R9(t) of the Dyson-Phillips expansion of the semigroup is compact, and the spectrum of transport operator AH consists of only finite isolated eigenvalues with finite algebraic multiplicities in a trip Γω. The main methods rely on theory of linear operators, comparison operators, and resolvent operators approach.